Guidelines to Facilitate Human-Wildlife Interactions in Conservation Translocations - Consorte-McCrea, Adriana; Kolipaka, Shekhar; Owens, Jacob R.; Ruiz-Miranda, Carlos R.; Waters, Siân (Frontiers in Conservation Science, 2022)
Species reintroductions and translocations are widely used management interventions to restore locally extinct or augment severely depleted species. In such projects, the human dimension issues that influence the success of these conservation interventions are encountered at five different stages of the project life cycle: 1) Planning 2) Initiation 3) Implementation 4) Ending Stage and 5) Post-exit. Overlooking or failing to consider the human dimension in any of these phases could jeopardize the conservation translocation project’s success. When the human dimensions are included there is greater possibility of community involvement, peers’ acceptance and support from various interest groups and avoidance of conflict situations. The Human-Wildlife Interactions Working Group (HWIWG) was formed in 2018 by members of the IUCN Conservation Translocation Specialist Group (CTSG). HWIWG has facilitated online discussions and workshops with practitioners, researchers and academics from across the globe, on a range of aspects of human-wildlife interactions in conservation translocations, as well as leading discussion sessions during international research conferences. These events have provided a rich source of material from which to draw a series of recommendations. In this paper we discuss findings from the HWIWG that illustrate how, in each of the five stages of the project life cycle, human-dimensions influenced conservation translocation projects. Our aim is to provide useful and multidimensional insights for those working in species’ reintroductions and translocations.